2019
DOI: 10.1186/s12910-019-0369-7
|View full text |Cite
|
Sign up to set email alerts
|

How should assent to research be sought in low income settings? Perspectives from parents and children in Southern Malawi

Abstract: Background Paediatric research in low-income countries is essential to tackle high childhood mortality. As with all research, consent is an essential part of ethical practice for paediatric studies. Ethics guidelines recommend that parents or another proxy provide legal consent for children to participate, but that children should be involved in the decision through providing assent. However, there remain uncertainties about how to judge when children are ready to give assent and about appropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
10

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 16 publications
0
10
0
10
Order By: Relevance
“…In the 30 studies focusing on opinions and perceptions of assent, the main populations studied were children (60%), parents (23.3%) [ 23 , 26 31 ], researchers (23.3%) [ 15 , 17 , 29 , 30 , 32 – 34 ] and healthcare professionals (16.7%) [ 15 , 22 , 23 , 30 , 31 ]. The main themes identified in these studies were: children’s desire to be involved and their empowerment [ 24 26 , 32 , 35 39 ], need for cultural considerations [ 12 , 17 , 18 , 26 , 28 , 30 , 31 , 40 ], specific context considerations and opinion variation [ 21 23 , 29 , 33 , 34 , 41 ] as well as need for age and developmental considerations [ 13 , 27 , 42 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the 30 studies focusing on opinions and perceptions of assent, the main populations studied were children (60%), parents (23.3%) [ 23 , 26 31 ], researchers (23.3%) [ 15 , 17 , 29 , 30 , 32 – 34 ] and healthcare professionals (16.7%) [ 15 , 22 , 23 , 30 , 31 ]. The main themes identified in these studies were: children’s desire to be involved and their empowerment [ 24 26 , 32 , 35 39 ], need for cultural considerations [ 12 , 17 , 18 , 26 , 28 , 30 , 31 , 40 ], specific context considerations and opinion variation [ 21 23 , 29 , 33 , 34 , 41 ] as well as need for age and developmental considerations [ 13 , 27 , 42 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies focused on pediatric assent practicalities and identified complexity and variability of assent practices [ 23 , 46 ], variability of clinicians and researchers’ knowledge about assent [ 22 , 33 ] as well as cultural and context-specific assent considerations [ 17 , 18 , 29 , 30 , 34 , 47 ] as important themes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A central component of much of the empirical ethics work across our institutions, which over time has been valuably supported, critically reviewed, and deepened through the GHBN, is engagement with community members and broader publics [25][26][27][28][29][30][31][32][33][34][35] . An immediate potential opportunity and need under COVID-19 was to work with established community engagement networks with whom we had long term relationships in order to: 1) learn about community members' and the broader publics' priorities and concerns in relation to the response, and to communicate these up through institutions and to local, national and global policy makers and influencers through our wider networks in order to inform locally tailored information giving and action; 2) seek community members' advice and inputs on how to manage closure or appropriate continuation of non-COVID-19 related studies; and 3) engage community members on prioritizing and planning COVID-19 studies.…”
Section: Responsibilities and Approaches To Engaging With Community M...mentioning
confidence: 99%